Magnetic properties of Ce-containing Pr/Nd-Fe-B sintered magnets by diffusing Nd-Dy-Al alloy - Liang, Liwei; Wang, Ruixiang; Chen, Dehai; Liu, Renhui; Ma, Pengfei; Wu, Tong; Wang, Haifeng (Frontiers in Materials, 2023)
5%wt-Ce-containing sintered Pr/Nd-Ce-Fe-B magnets were processed by grain boundary diffusion (GBD) with NdxDy90-xAl10 alloy (x=0, 10, and 20 correspond to N0, N10, N20, respectively). After GBD process, the coercivity of magnets increased from 1124.7 kA/m to 1656.4 kA/m, 1673.9 kA/m, and 1584.8 kA/m, for N0, N10, and N20, respectively. Microstructure analysis revealed continuous RE-rich intergranular phases around matrix grains, which weakening the magnetic coupling effect between ferromagnetic matrix grains thus leads to coercivity improvement. N10 had the same coercivity enhancement as N0, while the Dy utilization for the N10 is lower than the N0. SEM results showed that the inclusion of Nd leds to the formation of a network of low-melting grain boundary phases, providing channels for subsequent Dy diffusion. A CeFe2 phase was found in the 5%wt-Ce-containing magnet, which hindered diffusion due to its high melting point, in order to inhibit the negative impact of CeFe2 and reveal the diffusion mechanism in Ce-containing magnet, DyH3 as diffusion source was applied to 5%wt-Ce-containing magnets simultaneously, after GBD process, Nd10Dy90Al10 alloy as diffusion source has better coercivity enhancement than DyH3, due to the deeper diffusion of Dy element in the Nd10Dy90Al10 diffusion.